Bibliometric landscape of current research on acetoxychavicol acetate - Febri Wulandari, Muhammad Da’i, Ahmad Fauzi, Maryati Maryati, Mahmoud Mirzaei (Journal of Applied Pharmaceutical Science, 2025)
Acetoxychavicol acetate (ACA) is a promising natural compound with an extensive spectrum of medicinal properties. This study aimed to provide bibliometric mapping to evaluate the ACA trends in publishing and original research. We conducted a targeted search on the Scopus database for relevant literature and examined the acquired data using VOSviewer to determine the citation and keyword patterns. A total of 135 articles were examined. Over several years, research on the ACA has revealed a fluctuating pattern. Currently, Japan and Malaysia are the most prolific countries in studies related to ACA, and they also demonstrate the most extensive collaboration networks. Co-occurrence analysis of keywords revealed that anticancer phrases ranked the highest. This study provides a comprehensive overview of the current research landscape and outlines future expectations for the development of ACA as a drug candidate.
Keywords: Acetoxychavicol acetate (ACA), bibliometric mapping, VOSviewer, pharmacological activity, anticancer